Inquiry and Discovery Learning Model in Student's Mathematic Representation Ability - Imam Setiadi Putra (Universitas Islam Lamongan, 2023)
Representational ability is a very important ability in learning mathematics, with representational ability students can solve mathematical problems. This study aims to compare the two Inquiry and Discovery learning models in overcoming students' representation abilities. This research was conducted at a school in NTB Province, Bima Regency with a total of 60 students with a sample of 30 participants from Science 1 and 30 participants from Science 2. Data collection techniques used observation and interviews. While the instrument uses a test. Data analysis techniques used Prerequisite test (Normality and Homogeneity) and Hypothesis Test (N_Gain, t test). In terms of this research, it shows that during representation learning, these two models really help students to understand the use of mathematical representations.